THE EFFECT OF USING GAMIFICATION ON STUDENTS’ WRITING RECOUNT TEXT ABILITY - Yemima Tiur Simanjuntak; Angelina Monthesari Manullang; Setriani Sinaga; Mikael Stanley; Ananda Rizky Mulia (J-Shelves of Indragiri (JSI), 2026)
This research aims to determine: (1) the application of gamification method in teaching writing recount text, (2) students’ ability in writing recount text before and after using gamification, and (3) whether there is a significant effect of using gamification on students’ writing recount text ability at the ninth grade of SMP Negeri 3 Padangsidimpuan in the 2025/2026 academic year. This research uses a pre-experimental method with a one-group pre-test and post- test design. The population consists of 241 ninth-grade students, and 31 students were selected through purposive sampling. The instruments used are observation sheets and writing tests. The observation results show that the application of gamification is categorized as “Very Good” with a mean score of 3.92. The students’ mean score in writing recount text before using gamification was 36, categorized as “Fail,” while after using gamification, it increased to 73, categorized as “Good.” Based on the Wilcoxon Signed Rank Test, the result shows Asymp. Sig. (2-tailed) = 0.000 < 0.05, which means Ha is accepted. Therefore, it can be concluded that using Baamboozle as a gamification method gives a significant positive effect on students’ writing recount text ability at the ninth grade of SMP Negeri 3 Padangsidimpuan.